A cytogenetic analysis of male meiosis in Asparagus officinalis. Issue 4 (3rd April 2019) - Yuan, Jinhong; Yuan, Jiaojiao; Zhou, Huihui; Su, Qiaoqiao; Ji, Shuai; Li, Yuqing; Guo, Siyi; Li, Junhua
ABSTRACT: Asparagus ( Asparagus officinalis ) has several traits that make it a useful model for cytogenetic studies, however, few studies of the meiosis process have been made in asparagus. Here, we present in detail an atlas of male meiosis in asparagus, from preleptotene to telophase II. The meiosis process in asparagus is largely similar to those of the well-characterized model plants Arabidopsis thaliana, Zea mays, and Oryza sativa . However, most asparagus prophase I meiotic chromosomes show a strongly aggregated morphology, and this phenotype persists through the pachytene stage, highlighting a property in the control of chromosome migration and distribution in asparagus. Further, we observed no obvious banding of autofluorescent dots between divided nuclei of asparagus meiocytes, as one would expect in Arabidopsis . This description of wild-type asparagus meiosis will serve as a reference for the analyses of meiotic mutants, as well as for comparative studies among difference species. Abbreviations : DAPI: 4', 6-diamidino-2-phenylindole; FISH: fluorescence in situ hybridization; PBS: phosphate-buffered saline; PMC: pollen mother cell; SEM: Scanning Electron Microscope Graphical abstract: : Asparagus chromosomes (a) are in a more aggregated state than Arabidopsis (b), and lacking autofluorescent band between nuclei (c), as one would expect in Arabidopsis (d).